2019
DOI: 10.1016/j.ebiom.2018.11.020
|View full text |Cite
|
Sign up to set email alerts
|

Liver Iron Load Influences Hepatic Fat Fraction in End-Stage Renal Disease Patients on Dialysis: A Proof of Concept Study

Abstract: BackgroundNonalcoholic fatty liver disease (NAFLD) is a spectrum of diseases including steatosis, nonalcoholic steatohepatitis (NASH), cirrhosis, and end-stage liver failure. Hepatic iron accumulation has been linked to hepatic fibrosis severity in NASH and NAFLD. Iron overload induced by parenteral (IV) iron therapy is a potential clinical problem in dialysis patients. We analyzed the hypothetical triggering and aggravating role of iron on NAFLD in patients on dialysis.MethodsLiver iron concentration (LIC) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(48 citation statements)
references
References 41 publications
0
48
0
Order By: Relevance
“…Thus, considering the results of this study, especially the positive likelihood ratio and Fagan's nomograms, we advocate first for its ease of use as a tool for the detection of iron overload in the setting of dialysis the use of R2* relaxometry; second, in positive cases, taking into consideration the actual high prevalence of non-alcoholic fatty liver disease in the dialysis population [49] as the ability of excessive iron therapy to induce liver steatosis in ESKD [23], it seems of paramount importance to quantify the liver fat fraction and to obtain a reliable evaluation of liver iron content in this setting by multi-peak spectral modelling; third, in the case of confirmed liver iron overload (without important fat fraction), a quantification of LIC by SIR MRI is of high diagnostic interest; fourth, in case of severe iron overload on SIR MRI (LIC > 200 µmol/g of dry liver), a search for pancreatic and heart iron deposits is mandatory by R2* relaxometry.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Thus, considering the results of this study, especially the positive likelihood ratio and Fagan's nomograms, we advocate first for its ease of use as a tool for the detection of iron overload in the setting of dialysis the use of R2* relaxometry; second, in positive cases, taking into consideration the actual high prevalence of non-alcoholic fatty liver disease in the dialysis population [49] as the ability of excessive iron therapy to induce liver steatosis in ESKD [23], it seems of paramount importance to quantify the liver fat fraction and to obtain a reliable evaluation of liver iron content in this setting by multi-peak spectral modelling; third, in the case of confirmed liver iron overload (without important fat fraction), a quantification of LIC by SIR MRI is of high diagnostic interest; fourth, in case of severe iron overload on SIR MRI (LIC > 200 µmol/g of dry liver), a search for pancreatic and heart iron deposits is mandatory by R2* relaxometry.…”
Section: Discussionmentioning
confidence: 98%
“…The recent Proactive IV Iron Therapy in Haemodialysis Patients (PIVOTAL) trial has demonstrated strong evidence of a benefit of IV iron in the treatment of anaemia in ESKD, with decreased hospitalisation rates related to cardiac insufficiency and reduced ESA cost [20]. Conversely, while the PIVOTAL study will result in an increased use of parenteral iron in clinical practice, there is a need to take into account the double-edged sword of iron therapy [21], especially hepatic iron accumulation, which has been associated with increased hepcidin production and a risk of destabilising atheromatous plaques, triggering cardiovascular events [9][10][11]22] and inducing or worsening fatty liver disease [23], together with the increased mortality shown by Dialysis Outcomes and Practice Patterns Study (DOPPS) in ESKD patients receiving over 300 mg monthly IV iron [24].…”
Section: Introductionmentioning
confidence: 99%
“…[91]2018EgyptMRI-T2* relaxometry5025 patients suffering from hepatitis CHepatic siderosis in 22/50 (44 %) patientsMild iron overload = 14%Moderate iron overload = 16%Severe iron overload = 14%Rostoker et al. [90]2019FranceSIR-MRI for liver iron MRI-T2* relaxometry for fat fraction68 (62 on HD and 6 on PD)Patients treated according to ERBP Statement 2013 Ferritin target up to 300 μg/LHepatic siderosis in 39/68 patients (57%): mild in 23, moderate in 9 and severe in 7SQUID: superconducting quantum interference device; MRI: magnetic resonance imaging; LIC: liver iron concentration; SIR: signal intensity ratio; KDOQI: kidney disease outcomes quality initiative; ERBP: European renal best practice…”
Section: Main Textmentioning
confidence: 99%
“…Thus, the ability of Auryxia to deliver iron, because of its chemical composition, is an added benefit when it is already being used to control phosphate levels and may improve clinical outcomes that are unrelated to hyperphosphatemia. The benefit of Auryxia as a therapy for the treatment of iron deficiency may be particularly important in light of recent research that has implicated IV iron therapy in non-alcoholic fatty liver disease (NAFLD) [ 103 , 104 ]. In a longitudinal study of 7 patients undergoing IV iron therapy, hepatic proton density fat fraction and liver iron concentration levels increased significantly, suggesting that iron overload in these dialysis patients may have led to or exacerbated NAFLD [ 103 ].…”
Section: Clinical Characteristics Of Auryxiamentioning
confidence: 99%